Neuropsychiatry of atrial fibrillation: dementia and beyond - Chaudhari, Mayuresh; Rodriguez, Juan; Velasco, Alejandro; Agoston, Ildiko; Seshadri, Sudha; Teixeira, Antonio L. (Frontiers in Cardiovascular Medicine, 2025)
Atrial fibrillation (AF) is the most frequent heart rhythm disorder worldwide with a prevalence of 1%–2% in general population. It is associated with increased mortality and morbidity, including increased risk of dementia. In addition to cognitive impairment, AF has been related to anxiety and mood disorders. Herein we review the literature on the association between AF and neuropsychiatric conditions, including anxiety and mood disorders. The mechanisms underlying the association between AF and dementia are complex, including stroke, chronic cerebral hypoperfusion, and systemic inflammation. There is a bidirectional interaction between AF and anxiety/mood disorders with shared mechanisms involving dysfunction of the autonomic, neuroendocrine and immune systems. Optimizing pharmacological treatment, avoiding drug interactions and implementing behavioral interventions can have a lasting impact on patients with AF undergoing rhythm/rate control therapies and/or catheter ablation.